2013
DOI: 10.1093/cvr/cvt207
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-rich protein 2 alters p130Cas localization and inhibits vascular smooth muscle cell migration

Abstract: These studies demonstrate that CRP2 sequesters p130Cas at FAs, thereby reducing lamellipodia formation and blunting VSMC migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…MUC18 (CD146) is a glycoprotein detected in endothelial cells as a surface receptor that triggers a transient increase in the intracellular calcium concentration . Cysteine‐rich protein (CRP) 2 is a member of the LIM‐only CRP family, also expressed in vascular smooth muscle cells (VSMCs) of blood vessels . Its role is to repress VSMC migration and vascular remodelling, because it was demonstrated that the absence of CRP2 increases neointima formation, correlating with increased VSMC migration .…”
Section: Discussionmentioning
confidence: 99%
“…MUC18 (CD146) is a glycoprotein detected in endothelial cells as a surface receptor that triggers a transient increase in the intracellular calcium concentration . Cysteine‐rich protein (CRP) 2 is a member of the LIM‐only CRP family, also expressed in vascular smooth muscle cells (VSMCs) of blood vessels . Its role is to repress VSMC migration and vascular remodelling, because it was demonstrated that the absence of CRP2 increases neointima formation, correlating with increased VSMC migration .…”
Section: Discussionmentioning
confidence: 99%
“…These expression levels are relevant to IMT and plaque, as BCAR1 has been shown to be expressed at the protein level in cells involved in atherosclerosis. 25 Although analysis could not be separated by sex in GTEx, further analysis of tissue expression data in ASAP 8 did not indicate the association of rs4888378 with TMEM170A and LDHD to be specific to women; the relationship was significant in men but not in women ( Figure VI in the Data Supplement). However, the small sample size of women precluded assessment of any association.…”
mentioning
confidence: 95%
“…It has since been shown that BCAR1 is involved in PDGF stimulation of VSMC migration, and its expression and phosphorylation promote formation of neointima after arterial injury. 25 We therefore hypothesize that the risk G allele increases expression of BCAR1 stimulating VSMC migration and increasing the formation of neointima in the vessel wall, resulting in larger plaques and greater cIMT.The implication of BCAR1 in the phenotype is particularly interesting when we consider the sex-specific associations with common cIMT, IMT progression, and vascular events. Men have a higher overall risk of CHD, 28 and although differences between the sexes in traditional risk factors contribute to this disparity, sex remains associated over and above the known risk factors.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Cas is associated with the development and progression of pulmonary disease (8), cardiovascular disease (9), and particularly cancer (1,4,10,11). Increased p130…”
mentioning
confidence: 99%